Implementation of Student Satisfaction Information System to the Final Project Services - Rahimullaily Rahimullaily; Rahmadini Darwas; Afdiko Saputra (Sistemasi: Jurnal Sistem Informasi, 2022)
The final project service is a supervision service from the lecturer for students who